1982
DOI: 10.1002/1097-0142(19820515)49:10<2015::aid-cncr2820491012>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation treatment of carcinoma of the cervix with extension into the endometrium. A reappraisal of its significance

Abstract: During the period from 1969--1974, 561 patients with proven invasive squamous cell carcinoma of the cervix were treated by irradiation only in the Department of Radiation Therapy, University of Maryland Hospital. Of these, 82 patients were identified as having D & C positive for squamous cell cancer present in the curettings with or without endometrial tissue. Clinical staging was done using FIGO guidelines and the treatment of endometrial extension was the same as with regular cervical cancer. Of 82 cases who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…In previous studies, patients with endometrial extension have been shown to have a poor prognosis because of a higher rate of development of distant metastases, [2][3][4][5]18 but there was no explanation of this finding. Narayan et al has shown a correlation between magnetic resonance imaging (MRI) endometrial extension and FDG-PET-detected lymph nodes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies, patients with endometrial extension have been shown to have a poor prognosis because of a higher rate of development of distant metastases, [2][3][4][5]18 but there was no explanation of this finding. Narayan et al has shown a correlation between magnetic resonance imaging (MRI) endometrial extension and FDG-PET-detected lymph nodes.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we suggest that endometrial extension is correlated with lymph node metastases, which correlates with development of distant metastases and a worse prognosis. [2][3][4][5]18 In the absence of FDG-PET evaluation, evidence of endometrial extension may assist in assessing a patient-s risk of lymph node metastasis. This prognostic information may be useful in stratifying patients for risk-adjusted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of pelvic lymph node metastasis, increased risk of distant metastasis, high rates of recurrence, and poor survival in patients with uterine invasion of cervical cancer were highlighted in these previous studies. 3,[13][14][15] However, their small sample sizes and/or lack of evaluation procedures for proving uterine invasion in cervical cancer due to the probability of contamination in D&C were the alleged obstacles of these studies. [13][14][15][16] Despite that, studies redrew attention to the prognostic importance of uterine corpus invasion in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1). 1520 The relapse rate in those with PET-positive node disease has been reported to be approximately 50% after standard chemoradiation. 17,21,22 Some suggest that a follow-up fludeoxyglucose (FDG)-PET scan done 3 to 4 months postchemoradiation can predict patient outcome and may help to determine the intensity of follow-up needed.…”
Section: Nonsurgical Management Of Locally Advanced Cervical Cancermentioning
confidence: 99%